Randomized phase II trial comparing amrubicin with re-challenge of platinum doublet in patients with sensitive-relapsed small-cell lung cancer: North Japan Lung Cancer Study Group trial 0702. Issue 1 (July 2015) - Inoue, Akira; Sugawara, Shunichi; Maemondo, Makoto; Mori, Yoshiaki; Oizumi, Satoshi; Harada, Masao; Taima, Kageaki; Morikawa, Naoto; Ishida, Takashi; Kinoshita, Ichiro; Watanabe, Hiroshi; Suzuki, Toshiro; et al.
Highlights This randomized phase II was conducted to select a proper regimen for phase III. Amrubicin achieved a higher ORR and a longer PFS than re-challenge of platinum. Only amrubicin met the primary endpoint, which deserves further investigation. Toxicity was generally acceptable and no treatment-related death was observed.